2020
DOI: 10.1007/s00535-020-01710-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the immune milieu in gastrointestinal cancers

Abstract: Gastrointestinal (GI) cancers are among the most common and lethal solid tumors worldwide. Unlike in malignancies such as lung, renal and skin cancers, the activity of immunotherapeutic agents in GI cancers has, on the whole, been much less remarkable and do not apply to the majority. Furthermore, while incremental progress has been made and approvals for use of immune checkpoint inhibitors (ICIs) in specific subsets of patients with GI cancers are coming through, in a population of ‘all-comers’, it is frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 171 publications
0
4
0
Order By: Relevance
“…Additionally, the difference in the concentration of interleukin 7 (IL‐7) secreted by immune cells in the TME between GC and CRC (GC vs CRC: 61.6 pg/g vs. 88.6 pg/g) has been reported to be correlated with the digestive tract flora 16 . Therefore, the difference in the digestive tract flora may be one of the reasons for the difference between the two in TME immunity 14,17 . In addition, tumor cells in the TME will cause different degrees of immune activation in the peripheral blood, leading to different degrees of inflammatory response in the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the difference in the concentration of interleukin 7 (IL‐7) secreted by immune cells in the TME between GC and CRC (GC vs CRC: 61.6 pg/g vs. 88.6 pg/g) has been reported to be correlated with the digestive tract flora 16 . Therefore, the difference in the digestive tract flora may be one of the reasons for the difference between the two in TME immunity 14,17 . In addition, tumor cells in the TME will cause different degrees of immune activation in the peripheral blood, leading to different degrees of inflammatory response in the body.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Therefore, the difference in the digestive tract flora may be one of the reasons for the difference between the two in TME immunity. 14 , 17 In addition, tumor cells in the TME will cause different degrees of immune activation in the peripheral blood, leading to different degrees of inflammatory response in the body. Previous study found that the cutoff value of systemic immune‐inflammation index (SII) of CRC is different from that of GC (460.66 vs 660).…”
Section: Introductionmentioning
confidence: 99%
“…This will likely clarify some unsolved aspects of the interaction between MDSCs and GI cancer cells, laying the groundwork for more effective therapeutic strategies in the future. Finally, unlike in malignancies such as lung, renal, and skin cancers, the efficacy of immunotherapeutic agents on GI cancer has, on the whole, been much less remarkable and do not apply to the majority [166]. This could be explained by the permeated MDSCs in the tumor microenvironment, which eliminated the response of activated T cells generated by PD1/PD‐L1 blockade.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…However, chemotherapeutic drugs often have disadvantages such as poor water solubility, low tumor targeting ability, and severe adverse reactions, which greatly limit their clinical applications [3]. At the same time, because most cases are found in the late stage of the disease, the effective treatment methods are very limited, resulting in a high fatality rate [4][5][6][7]. Therefore, exploring new therapeutic methods for digestive system cancer has become a hotspot of current research.…”
Section: Introductionmentioning
confidence: 99%